2019
DOI: 10.1093/jac/dkz277
|View full text |Cite
|
Sign up to set email alerts
|

MSG-10: a Phase 2 study of oral ibrexafungerp (SCY-078) following initial echinocandin therapy in non-neutropenic patients with invasive candidiasis

Abstract: Objectives To evaluate the safety and efficacy of two dosing regimens of oral ibrexafungerp (formerly SCY-078), a novel orally bioavailable β-glucan synthase inhibitor, in subjects with invasive candidiasis versus the standard of care (SOC) and to identify the dose to achieve target exposure (15.4 μM·h) in >80% of the intended population. Methods In a multinational, open-label study, patients with documented invasive candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 15 publications
0
49
0
1
Order By: Relevance
“…Animal studies looking at the tissue distribution of ibrexafungerp achieved high concentrations in the skin, an attribute that may be of importance to limit C. auris skin colonization, with a potential impact of limiting transmission. Ibrexafungerp demonstrates activity across a range of invasive fungal diseases as a monotherapy but also in combination [ 58 , 59 ]. Early clinical evidence from an emergency-use Phase 3 study of ibrexafungerp for invasive candidiasis due to C. auris is promising.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies looking at the tissue distribution of ibrexafungerp achieved high concentrations in the skin, an attribute that may be of importance to limit C. auris skin colonization, with a potential impact of limiting transmission. Ibrexafungerp demonstrates activity across a range of invasive fungal diseases as a monotherapy but also in combination [ 58 , 59 ]. Early clinical evidence from an emergency-use Phase 3 study of ibrexafungerp for invasive candidiasis due to C. auris is promising.…”
Section: Discussionmentioning
confidence: 99%
“…Phase II studies previously utilized a 1250 mg PO once loading dose. It has been well-tolerated in studies and primarily limited to gastrointestinal adverse effects, with several studies identifying no significant difference from placebo arms [20].…”
Section: Ibrexafungerpmentioning
confidence: 99%
“…It is currently being evaluated in an open-label, non-comparator, single arm phase III study as treatment of invasive fungal disease refractory or intolerant to standard-of-care therapy (FURI; NCT03059992), a phase III study vs placebo in patients with recurrent vulvovaginal candidiasis (CANDLE; NCT04029116). Interim analysis of the study has identified clinical benefit in 17 of the 20 evaluated patients [20].…”
Section: Ibrexafungerpmentioning
confidence: 99%
“…This drug might be considered for future randomized trials as an oral stepdown agent. 82 Fosmanogepix (previously APX001) is a first-in-class broad-spectrum antifungal drug with in vitro and in vivo activity against Candida, including C. auris. Its active moiety APX001A targets the highly conserved fungal enzyme Gwt1, which mediates the cross-linking of cell-wall mannoproteins to β-1,6-glucan.…”
Section: New Antifungalsmentioning
confidence: 99%